Type I interferon in anti‐MDA5 dermatomyositis. (26th April 2019) - Zhang, S.H.; Zhao, Y.; Xie, Q.B.; Jiang, Y.; Wu, Y.K.; Yan, B.
Summary: Dermatomyositis (DM) is a rare condition which causes inflammation in the skin and muscles. There are different subtypes of DM, which are defined by genetic differences. One subtype of DM, characterised by a gene called anti‐melanoma differentiation‐associated gene 5 (anti‐MDA5 DM), is linked to an extremely high risk of interstitial lung disease (ILD). In Asia, 10‐48% of DM patients have this type of DM. This study, from China, aimed to explore the role of certain proteins, together known as the type 1 interferon system, in development of this type of DM. Patients with anti‐MDA5 DM were studied and compared with patients who suffered from other variations of DM. The levels of specific proteins in the blood (inflammatory cytokines, B cell activating factor or 'BAFF', Krebs von den Lungen‐6) and in skin lesions (STAT1, ISG15 and MxA) were tested. The levels of the protein plasma IFN‐α was much higher in anti‐MDA5 DM patients than those of other DM subtypes. Skin biopsies from anti‐MDA5 DM patients were characterized by the strong expressions of (presence of) STAT1, ISG15, and MxA proteins. In the anti‐MDA5 DM/ILD patients with high IFN‐α production, there was a relationship between IFN‐α and BAFF levels. In addition, the higher levels of BAFF paralleled to the higher concentrations of KL‐6. This study confirms the abnormal activation of type I IFN protein system in anti‐MDA5 DM. Overproduction of IFN‐α linked with BAFF may be implicated in the development of ILD. Abstract : Linked Article:  Zhang et al. Br J Dermatol 2019; 180 :1090–1098